Spam review detection - Tan, Hui Min. (2013)
As more people depend heavily on the information presented on the web, user generated content like reviews could easily influence the purchase decisions of other consumers. As such, multiple fake reviews have been frequently posted to various popular online review websites to mislead the consumers.